A MULTI-PROXY STUDY OF ARGENTINA LOESS: MARINE OXYGEN ISOTOPE STAGE 4 AND 5 ENVIRONMENTAL RECORD FROM PEDOGENIC HEMATITE - Carter-Stiglitz B.; Banerjee S.K.; Gourlan A.; Oches E. (My University, 2006)
A 12 m loess–paleosol section (La Angostura) from Tafi del Valle, Tucumán, Argentina was studied using rock magnetic measurements, geochemistry, Mössbauer effect, particle size and Nd isotopes in order to elucidate changes in paleoenvironment at the site. Combining the results of these experiments allowed us to separate the effects of the two major controls (parent material and pedogenesis) on the measured parameters. Two behavior regimes were identified in the sediment: 1) in the lower half of the section pedogenic processes, though weak, dominate the variation of the sediment's physical properties, and 2) for the upper half of the section subtle changes in parent material control the majority of the measured parameters, even those typically controlled by pedogenesis, e.g., clay fraction. Applying rock magnetic, Mössbauer, and bulk geochemistry measurements in concert we calculated an iron budget for the loess. ∼80% of the iron in the sediment is in paramagnetic minerals; ∼20% of the iron is in hematite (∼1.6% of the sediment's mass), and ≪ 1% of the total iron is present as magnetite/maghemite (∼0.1% of the sediment's total mass). Neither the pedogenic formation nor the depletion of ferrimagnetic material with increasing pedogenesis was consistently observed in this sediment. Throughout the entire section the concentration of hematite is argued to be sensitive to in situ alteration, and it is further surmised to be sensitive to the available moisture at the site. Finally we present a curiosity: within the error of our chronology,